Theory and Practice in Late Antique Archaeology
1 online resource.
Keywords: Can ideas and approaches current in mainstream archaeology be made to work in the conservative world of classical archaeology? This volume seeks to explore theoretical frameworks, methodology and field practice suited to the late antique Mediterranean. Broad themes such as long-term change, topography, the economy and social life are covered, but in terms of specific issues and evidential problems currently being tackled by scholars of late antiquity. This book will be useful to students and researchers seeking to enrich their approaches to Mediterranean historical archaeology and to anyone wishing to possess an overview of the current state of late antique archaeology.